Shear loads induce cellular damage in tendon fascicles. Issue 12 (18th September 2015) - Kondratko-Mittnacht, Jaclyn; Lakes, Roderic; Vanderby, Ray
Abstract Tendon is vital to musculoskeletal function, transferring loads from muscle to bone for joint motion and stability. It is an anisotropic, highly organized, fibrous structure containing primarily type I collagen in addition to tenocytes and other extracellular matrix components contributing to maintenance and function. Tendon is generally loaded via normal stress in a longitudinal direction. However, certain situations, including fiber breakage, enzymatic remodeling, or tendon pathology may introduce various degrees of other loading modalities, such as shear-lag at the fiber level, potentially affecting cellular response and subsequent function. Fascicles from rat tail tendon were dissected and placed in one of three paired groups: intact, single laceration, or double laceration. Each pair had a mechanically tested and control specimen. Single laceration fascicles contained one transverse laceration to mimic a partial tear. Double laceration fascicles had overlapping, longitudinally separated lacerations on opposite sides to cause intra-fascicular shear transfer to be the primary mechanism of loading. Elastic properties of the fascicle, e.g. peak load, steady state load, and stiffness, decreased from intact to single laceration to double laceration groups. Surprisingly, 45% of the intact strength was maintained when shear was the primary internal load transfer mechanism. Cellular viability decreased after mechanical testing in both laceration groups; cell death appeared primarily in a longitudinal plane where high shear load transfer occurred. This cell death extended far from the injury site and may further compromise an already damaged tendon via enzymatic factors and subsequent remodeling associated with cell necrosis.